The Comparative Method in Legal Research of the Cryptoasset Market - Larisa V. SANNIKOVA; Julia S. KHARITONOVA (Communications of International Proceedings, 2020)
The article explains the use of the comparative method to the research the cryptoasset market. The question of the purpose of using this method in legal research remains debatable. Despite the differences in comparative approaches, most scientists agree to define comparative legal research's main practical goals: legal transplantation and harmonization of legislation. In many states, legislators and legal experts are faced with the need to solve global problems related to the regulation of crypto-assets, which requires rethinking the use of the comparative method. To date, no country in the world can claim that it has formed the optimal legal regulation of crypto assets, with breakthrough potential. Analysis of the legislation on the blockchain and crypto-assets in Malta, Liechtenstein, and Russia shows significant conceptual differences. That indicates, first of all, that at the moment, there is no standard approach and understanding of the legal essence of crypto assets, which provides a possibility to form a complete and consistent regulation of this area. At the same time, significant harmonization was achieved by States united in solving the most critical supplementary task such as the fight against money laundering. The article concludes that the study of legal phenomena that are essentially cross-border at the current stage should take into account the legal regulation that is being formed both within the legislation of the most technologically advanced countries and in the international economic space. For this, it is necessary to use the method of comparative legal research.